ANALISIS THEORY ACCEPTANCE MODEL TERHADAP SISTEM INFORMASI AKUNTANSI BERBASIS WEB MENGGUNAKAN FRAMEWORK LARAVEL (Studi Kasus: CV Duta Square Bandar Lampung) - Neny Desriani; Dina Munjiati; Astria Hijriani (Jurnal Akuntansi Bisnis dan Ekonomi, 2021)
Accounting Information System is a Management Information System tool that provides accounting and financial information and other information obtained from routine processing of accounting transactions. The Accounting Information System tracks a large amount of information regarding sales orders, sales in units and currencies, cash collection, purchase orders, receipt of goods, payments, and salaries. Accounting Information Systems can be specifically designed for each organization, both commercial and non-commercial organizations. In this research the method used is the Scrum method, Scrum is a framework used to manage complex product development, which can use a variety of processes and techniques in it. Scrum has been used to develop software, hardware, integrated software and applications in interacting networks. The purpose of this research is to build and implement an Accounting Information System that fits the accounting cycle to provide financial reports in CV Duta Square. Accounting Information System at CV Duta Square Bandar Lampunng has been developed by providing several features, while those features are account data management, determining the reporting period, making general journals along with general journal details, posting to ledgers, and presenting financial reports.